2017
DOI: 10.15171/jnp.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cytomegalovirus disease in seropositive renal transplant recipients; a single-center case-controlled study

Abstract: Background: Risk factors for cytomegalovirus (CMV) disease in renal transplant recipients have been evaluated in industrialized countries with relatively low CMV seroprevalence. Objectives: We aimed to determine which factors are related to this illness in a high CMV seroprevalence country. Patients and Methods: A case-control study was performed with data from a 5-year follow-up of 260 kidney transplant recipients at our center. Odds ratios were calculated using the Mantel-Haenszel method. Results: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Patients who acquire CMV from their transplant donor (donor positive/recipient negative, D+/R‐) are at the highest risk of infection and generally receive 6 months of valganciclovir prophylaxis 17–20 . Recipients who have had an infection with CMV prior to transplantation (R+ HTR) are considered intermediate risk unless they receive antilymphocyte agents such as thymoglobulin for induction or rejection 21–23 . Their risk of CMV is less clear, with estimates in prior studies ranging widely 24–29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who acquire CMV from their transplant donor (donor positive/recipient negative, D+/R‐) are at the highest risk of infection and generally receive 6 months of valganciclovir prophylaxis 17–20 . Recipients who have had an infection with CMV prior to transplantation (R+ HTR) are considered intermediate risk unless they receive antilymphocyte agents such as thymoglobulin for induction or rejection 21–23 . Their risk of CMV is less clear, with estimates in prior studies ranging widely 24–29 .…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 , 19 , 20 Recipients who have had an infection with CMV prior to transplantation (R+ HTR) are considered intermediate risk unless they receive antilymphocyte agents such as thymoglobulin for induction or rejection. 21 , 22 , 23 Their risk of CMV is less clear, with estimates in prior studies ranging widely. 24 , 25 , 26 , 27 , 28 , 29 Practice varies in these patients with many receiving 3‐6 months of prophylaxis but others undergoing virologic monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age was also considered as the main risk factor of development of symptomatic infection [9, 39, 40]. However, in our cohort, we found that the young patients were more likely to have symptomatic viral reactivation (28.75 ± 5.12 vs. 38.09 ± 12.34, p < 0.007).…”
Section: Discussionmentioning
confidence: 52%
“…Проведенные исследования позволили выявить широкую распространенность цитомегаловирусной инфекции у пациентов, перенесших трансплантацию солидных органов. Так, ДНК ЦМВ была обнаружена у 46,7±3,9% пациентов, перенесших пересадку почки, и у 28,6±3,6% реципиентов печени, что согласуется с данными аналогичных исследований [9,11,16,23]. Следует отметить, что уровень серопозитивности у подавляющего большинства реципиентов солидных органов был достоверно высоким Рисунок 3.…”
Section: Discussionunclassified